2019
DOI: 10.1088/1367-2630/ab3f70
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal oscillation of an ion beam extracted from a potential-oscillating plasma source

Abstract: A radiofrequency oscillation is successfully superimposed on a plasma potential of a filamented source plasma in an ion beam source while maintaining a constant plasma density, in order to investigate effects of oscillating source plasma potential on an extracted ion beam. The experiment is preliminarily performed with a positive argon ion beam source. A class-D amplifier operational over a wide range of a frequency from a few tens of kHz to several MHz is installed; leading the oscillation of the plasma poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This has been verified by artificially superimposing the oscillating potential on the filamented source plasma in the positive ion beam source, where the spatiotemporal profile of the ion beam current downstream of the grids has been measured as shown in Fig. 14 [80]. No visible oscillation at the beam core has been detected, while the beam current in the peripheral region (sometimes called a 'beam halo') is found to oscillate by the rf potential oscillation.…”
Section: Fusion-relevant Plasmasmentioning
confidence: 75%
“…This has been verified by artificially superimposing the oscillating potential on the filamented source plasma in the positive ion beam source, where the spatiotemporal profile of the ion beam current downstream of the grids has been measured as shown in Fig. 14 [80]. No visible oscillation at the beam core has been detected, while the beam current in the peripheral region (sometimes called a 'beam halo') is found to oscillate by the rf potential oscillation.…”
Section: Fusion-relevant Plasmasmentioning
confidence: 75%
“…In addition, it should be noted that the beamlet core is affected by the source plasma fluctuation, which differs from the experimental observation with the positive ion source. 24) Therefore, the source plasma stability is also of crucial importance for the negative ion beamlet focusing.…”
Section: Discussionmentioning
confidence: 99%
“…22,23) In a positive ion source, it is observed that the oscillation of a beam halo is induced by the potential oscillation of the source plasma. 24) In the present study, we focus on the evaluation of the stability of the beam focusing. For this purpose, the external perturbation is applied to a filament-arc-type negative ion source and the time dependent change of the negative ion beam width has been experimentally measured and compared with the source plasma oscillation.…”
Section: Introductionmentioning
confidence: 99%